2014
DOI: 10.1590/1413-81232014198.07642013
|View full text |Cite
|
Sign up to set email alerts
|

Impacto das mudanças vocais e auditivas na qualidade de vida de idosos ativos

Abstract: Impacto das mudanças vocais e auditivas na qualidade de vida de idosos ativosInfluence of voice and hearing changes in the quality of life of active elderly individuals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 38 publications
3
16
0
13
Order By: Relevance
“…Similar results were observed in a study (24) evaluating the self-perception of active elderly adults regarding the impact of hearing changes on daily life and quality of life.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were observed in a study (24) evaluating the self-perception of active elderly adults regarding the impact of hearing changes on daily life and quality of life.…”
Section: Discussionsupporting
confidence: 88%
“…Studies reveal the non-perception of changes in vocal parameters as a consequence of healthy aging, because such changes do not interfere greatly in the communicative performance and on the voice-related quality of life 21,22 . These studies converge with the present research, in which most of the elderly showed a positive assessment regarding their own voices and showed no perception of changes in the voicerelated quality of life.…”
Section: Rd Category Of Analysis -Auditory Perception In Institutionmentioning
confidence: 99%
“…In order to maintain an active aging, it is necessary to have good functional capacity, where there is a socially active life with great possibilities of communication, in which the elderly have the opportunity to express themselves, which will give them greater social interaction with other individuals 5 .…”
Section: Introductionmentioning
confidence: 99%